2016
DOI: 10.1002/anie.201609731
|View full text |Cite
|
Sign up to set email alerts
|

Phototriggered Secretion of Membrane Compartmentalized Bioactive Agents

Abstract: A strategy for the light-activated release of bioactive compounds (BODIPY, colchicine, paclitaxel, and methotrexate) from membrane-enclosed depots is described. We have found that membrane permeable bioagents can be rendered membrane impermeable via covalent attachment to cobalamin (Cbl) through a photo-cleavable linker. These Cbl-bioagent conjugates are imprisoned within lipid-enclosed compartments in the dark, as exemplified by their retention in the interior of erythrocytes. Subsequent illumination drives t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…The Cy5–B12‐TAX conjugate 2 was prepared from a chemically modified derivative of B12 ( 1 ) . In brief, the three‐step procedure includes condensation of N‐Deboc docetaxel with the free carboxylate of 1 , removal of the Fmoc protecting group, and a final condensation of the exposed amine with the N‐hydroxysuccinimide activated form of Cy5 (Scheme S1, Figure S1, Supporting Information) . Alkyl‐cobalamins are photolyzed only at the wavelengths absorbed by the corrin ring (330–575 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The Cy5–B12‐TAX conjugate 2 was prepared from a chemically modified derivative of B12 ( 1 ) . In brief, the three‐step procedure includes condensation of N‐Deboc docetaxel with the free carboxylate of 1 , removal of the Fmoc protecting group, and a final condensation of the exposed amine with the N‐hydroxysuccinimide activated form of Cy5 (Scheme S1, Figure S1, Supporting Information) . Alkyl‐cobalamins are photolyzed only at the wavelengths absorbed by the corrin ring (330–575 nm).…”
Section: Resultsmentioning
confidence: 99%
“…[118] Rational redesign, to attach the fluorophore antenna to the hydroxy group on the ribose ring of vitamin-B12, allowed for attachment of therapeutics to the photocleavable position to produce pro-drugs and nanotherapeutics. [119,120] The phototriggered release of alkyl radicals from the Co-C of vitamin B12 bond has also been exploited for the photopolymerization of hydrogels, to encapsulate live cells. [121] The radical system demonstrated that far-red absorbing photoinitiators Reproduced with permission.…”
Section: Photochemical Bond Cleavage: "Photo-uncaging"mentioning
confidence: 99%
“…Echogenic polymer bubbles andD OX-loaded vesicless usceptible to focusedu ltrasound liberation, co-delivered in macrophages,r esulted in substantialt umor uptake, while free NP-DOX largely accumulated in the liver;t he cell-based agents penetrated 150 mmf rom the nearest blood vessel, however NPs were limited to 10-15 mm. [22] Photo-release of drugs has been used with red, farred, and near-IR light in erythrocytes, [24,63] which can uptake entitiesa sd escribed in further detail below.I ron oxide nanoparticles phagocytosed by macrophages can also assist in "directing" cellular delivery via magnetic resonance imaging [64] or electromagnetic actuation. [65] Cargo-bearing cells loaded in this manner have been utilized to cross the blood-brain-barrier.I nt he delivery of drug-laden nanoparticles for the treatmento fg lioma, macrophage viability was not affected at doxorubicin concentrations up to 25 mgmL À1 and drug-loaded nanoparticles exhibited better tumor targetinge fficiency and penetration.…”
Section: Phagocytosis Internalization and Transfectionmentioning
confidence: 99%
“…HD has been employed to load therapeutic enzymes, [27,67] nanoparticles, [48] and drugs. [63,68] These same ("blood-banking") conditions are also used for blood storage and transfusion. An apparatus, termed a" Red Cell Loader" (Sorin Group, Italy) has been developed to automate the process, and used to encapsulate av ariety of drugs.…”
Section: Phagocytosis Internalization and Transfectionmentioning
confidence: 99%
See 1 more Smart Citation